2019
DOI: 10.2134/cftm2019.07.0055
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Winter Barley in Minnesota: Relationships among Cultivar, Fall Seeding Date, Winter Survival, and Grain Yield

Abstract: No planting date from early September to mid-October consistently resulted in maximum winter survival.• Two key environmental variables, fall growing degree days and snow cover at or below -4°F contributed to winter survival.• The cultivar McGregor had the highest winter survival and grain yield among the cultivars tested.• Winter survival was positively associated with grain yield.• Additional research and breeding for winter hardiness will be needed to improve winter survival and grain yield. AbstractWinter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 24 publications
(32 reference statements)
1
25
0
Order By: Relevance
“…Many experiments have been performed in much drier conditions [16][17][18][19][20]22,24,39] or with spring planted cultivars [3,16,17,22,24,39]. Furthermore, many studies have found substantial differences in malting quality even in winter malting barley cultivars [10,11,14,18]. Caution should be used when generalizing experimental results given the diversity of growing conditions across North America and the relative novelty of winter malting barley cultivation in the Northeast.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many experiments have been performed in much drier conditions [16][17][18][19][20]22,24,39] or with spring planted cultivars [3,16,17,22,24,39]. Furthermore, many studies have found substantial differences in malting quality even in winter malting barley cultivars [10,11,14,18]. Caution should be used when generalizing experimental results given the diversity of growing conditions across North America and the relative novelty of winter malting barley cultivation in the Northeast.…”
Section: Discussionmentioning
confidence: 99%
“…This experiment indicated that even though malting barley is quite sensitive to nitrogen level in grains [13,14,18], leguminous crops may be grown before winter malting barley without damaging the yield or malting quality of the barley crop (Table 5). This result differs somewhat from research on malting barley production following legume cover crops further north in New England.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most notably, over 50% of the 2014 barley crop in New York and the 2019 crop in Ohio were injured as a result of the polar vortex (Sonnenberg, 2019; Verbeten, Ganoe, O'Dea, Bergstrom, & Sorrells, 2014). Temperature fluctuations, reduced snow cover, and soil heaving during the winter and spring create challenges in the survival of winter malting barley, generating uncertainty among farmers regarding their crop's yield potential (Zhong, Wiersma, Sheaffer, Steffenson, & Smith, 2019).…”
Section: Previous Studies On Stand Assessment Methodsmentioning
confidence: 99%
“…Reducing soil temperature at a depth of occurrence of tillering node to -10 ─ -14°C leads as a rule to whole frost-killing of plants. Crops of early sowing dates are the most vulnerable in winter period so they often outgrow and loose stability to low temperatures very fast, especially without snow covering [8][9][10][11][12][13]. In view of this information grain-producers attend high profile not only to right choice of sort structure of winter barley; there must be connected organically high indices of yield, drought-resisting and firmness to diseases and pests, but also they pay attention to growing technology that finally determines productivity of this crop [14].…”
Section: Introductionmentioning
confidence: 99%